Dissecting the cellular architecture and genetic circuitry of the soybean seed - Julie M. Pelletier; Min Chen; Jer-Young Lin; Brandon Le; Ryan C. Kirkbride; Jungim Hur; Tina Wang; Shu-Heng Chang; Alexander Olson; Lachezar Nikolov; Robert B. Goldberg; John J. Harada (Proceedings of the National Academy of Sciences, 2025)
Seeds are complex structures composed of three regions, embryo, endosperm, and seed coat, with each further divided into subregions that consist of tissues, cell layers, and cell types. Although the seed is well characterized anatomically, much less is known about the genetic circuitry that dictates its spatial complexity. To address this issue, we profiled mRNAs from anatomically distinct seed subregions at several developmental stages. Analyses of these profiles showed that all subregions express similar diverse gene numbers and that the small gene numbers expressed subregion specifically provide information about the biological processes that occur in these seed compartments. In parallel, we profiled RNAs in individual nuclei and identified nuclei clusters representing distinct cell identities. Integrating single-nucleus RNA and subregion mRNA transcriptomes allowed most cell identities to be assigned to specific subregions and cell types and/or cell states. The number of cell identities exceeds the number of anatomically distinguishable cell types, emphasizing the spatial complexity of seeds. We defined gene coexpression networks that underlie distinct biological processes during seed development. We showed that network distribution among subregions and cell identities is highly variable. Some networks operate in single subregions and/or cell identities, and many coexpression networks operate in multiple subregions and/or cell identities. We also showed that single subregions and cell identities possess several networks. Together, our studies provide unique insights into the biological processes and genetic circuitry that underlie the spatial landscape of the seed.